DEVELOPMENT OF AN INSTRUCTIONAL LEADERSHIP MODEL TO ENHANCE INSTRUCTIONAL PRACTICES IN GENERAL EDUCATION COURSES AT AN INTERNATIONAL UNIVERSITY - THAVILABH, UMA; ASAVISANU, POONPILAS (Scholar: Human Sciences, 2022)
This study focused on critical thinking in the context of general education. The aim of the study was the development of an instructional model. Qualitative and quantitative methods were employed in order to determine the expected instructional practices for enhancing university students’ critical thinking skills. Data on the current and expected instructional practices of the general education instructors was collected. Perceptions by students on these instructional practices was also collected. Participants included 23 instructors and 361 students teaching at and enrolled in general education courses at Assumption University in the 2020 academic year. The data was analyzed using gap analysis with the Mean Difference (MD) and the Priority Needs Index Modified in order to determine the gap between the expected and current instructional practices of general education instructors as well as the gap between the current instructional practices and student’s perceptions towards their instructor’s current instructional practices. The paired samples t-Test revealed significant differences between the mean scores of current instructional practices and the perceptions of students towards the instructors’ instructional practices in general education courses. There was a significant difference in all means from the three constructs in the instructors’ and students’ surveys at the .05 level of significance. The independent samples t-Test also showed significant differences in three major constructs related to current instructional practices (X̄ = 3.74, SD = .40) and student’s perceptions towards the instructors’ instructional practices in general education courses (X̄ = 3.13, SD = 1.31). A final model was developed from the significant findings and validated by experts.